(untitled) (Bangladesh Journal of Medical Science, 2021)
Induced lactation is a process of producing breast milk in non-puerperal women. There are various reasons for adoptive mothers to breastfeed their adopted child through induced lactation method. For Muslim communities, the main motivating factor for an adoptive mother to breastfeed their adopted child is to establish a mahram relationship. The mahram relationship allows the adopted child to interact with other family members as if they are biologically related. The mahram relationship is achieved when adoptive mothers give breastmilk to the adopted child aged less than two years old for at least five satisfying feedings. In this paper we report the journey of two women who went through the induced lactation process in order to achieve mahram relationship with their adopted infant. In both cases, the mothers were finally able to produce milk, feed their adopted infant and reach mahram relationship. Bangladesh Journal of Medical Science Vol.20(4) 2021 p.918-922